Synergetic Effect of TiO2–PCC/Zeolite Nanocomposite on the Photodegradation of Phenolic Compound in Wastewater - Dessy Ariyanti; Dio Fachry Rezky; Stephanus Dwipa Puja Rosariastoko; Dina Lesdantina; Erwan Adi Saputro; Fazlena Hamzah (ASEAN Journal of Chemical Engineering, 2025)
Phenol is an organic compound commonly found in the water bodies contained polluted wastewater from industrial, agricultural, and domestic activities. This compound exhibits carcinogenic properties and can impact human health at certain concentrations. Therefore, excessive phenol must be degraded. Various techniques dealing with phenol waste have been developed, including the adsorption method. However, secondary pollutants might form after the adsorption process. One potential alternative for handling phenolic compounds in wastewater without generating secondary waste is the photocatalytic process. It has been proven that, when combined with adsorption, the degradation activity can be enhanced. In this paper, phenol degradation was investigated by carrying out degradation using a semiconductor catalyst, such as TiO2, that synergizes with adsorbents like precipitated calcium carbonate (PCC) and zeolite. The highest phenol degradation was achieved with the variables 80% TiO2 - 20% PCC and 80% TiO2 - 20% zeolite, resulting in 74.3% and 69.22% of phenol degradation, respectively. In comparison, the TiO₂–PCC nanocomposite exhibits superior performance to the TiO₂–zeolite nanocomposite. The observation of the functional groups revealed that PCC has a larger functional group area, supporting the synergy of the adsorption-photocatalysis process compared to the TiO2–zeolite nanocomposite.